NEW LIGHT ON ‘DARK AGE’ POTTERY: A NOTE ON FINDS FROM SOUTH-WESTERN TURKEY - Vroom, Joanita (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper sets out to present some Late Antique and Early Medieval ceramic finds from excavations in Lycia in south-western Turkey, and in particular ceramic finds from the urban site of Limyra in eastern Lycia. First, a general overview will be given of the percentages of the quantified ceramic assemblages from several excavation trenches, which were excavated between 1993 and 1999 in the eastern part of Limyra. In addition, an attempt will be made to put the pottery finds from Limyra in a broader context (while especially looking at similar excavated examples on Lycian and adjacent Turkish sites), as well as to present some ceramic material of the so-called ‘Dark Age’ period.